Audre's daughter: Black lesbian steganography in Dee Rees' Pariah and Audre Lorde's Zami: A New Spelling of My Name. Issue 2 (2nd April 2016) - Kang, Nancy
ABSTRACT: This article argues that African-American director Dee Rees' critically acclaimed debut Pariah (2011) is a rewriting of lesbian poet-activist Audre Lorde's iconic "bio-mythography" Zami: A New Spelling of My Name (1982). The article examines how Rees' work creatively and subtly re-envisions Lorde's Zami by way of deeply rooted and often cleverly camouflaged patterns, resonances, and contrasts. Shared topics include naming, mother–daughter bonds, the role of clothing in identity formation, domestic abuse, queer time, and lesbian, gay, bisexual, and transgender legacy discourse construction. What emerges between the visual and written texts is a hidden language of connection—what may be termed Black lesbian steganography —which proves thought-provoking to viewers and readers alike.